(3GdMGTjI GdTQjajI Ydi TQM GdTeSjIs - (3GdLQLGfj, GdTQja GdLQLGfj, Ydj Hf eMeO Hf Ydj, J(B816(3g`s
(3ChdgG (B:s
(3bhdg hQJHg Ydi ebOeI hKdGK ebGdGJ hNGJeI Cbhd hgcPG hLOfG aj YHGQI GdeJf(B...s
(3BNQgG (B:s
...(3hdjcf gPG BNQ eG CQOfG EjQGOg(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B7s
(3GdPQjYI(B:(3L(B6(3,U(B54 (3,JMJ Qbe (B374s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs